AN INTEGRATED MODEL FOR TRANSLATING LEGAL TEXTS - Kocbek, Alenka (Vertimo studijos, 2017)
The paper proposes a model for translating legal texts which is intended to direct the translation process through a series of stages to the final product—a skopos-oriented target text in which the potential pitfalls resulting from translating between different legal languages and systems have been considered. The model unites different translation stances (Snell-Hornby’s integrated approach, the functionalist views with the skopos theory and the concept of cultureme, as well as Chesterman’s theory of memes) with the findings of comparative law regarding differences between legal systems and their impact on legal languages. It consists of ten stages, each addressing one of the specific linguistic and extralinguistic aspects of legal text types. When translating legal texts, a very specific situation may arise with respect to the cultural embeddedness of the target text, since memes of different legal cultures may co-exist on its various levels. This is especially the case when the parties involved in legal communication occurring through translation decide to use a third language as a lingua franca, which may lack any direct correlation with the legal culture(s) underlying such communication.